Nice work if you can get it: Labour market pathways of Belgian service voucher workers. (February 2023) - Lens, Dries; Marx, Ive; Oslejová, Jarmila; Mussche, Ninke
Seen as an alternative to precarious, informal work or no job at all, several European countries have started to use tax money to boost the demand for domestic services. This article asks whether this makes sense. We consider the case of the heavily subsidized and highly popular service voucher scheme in Belgium. Close to a quarter of households there employ domestic service workers under the scheme, making it in relative terms the largest scheme of its kind in Europe. The workers employed under the scheme enjoy extensive labour and social security rights. Does the service voucher scheme provide a model to be followed if we care about labour market exclusion and precariousness or is this a case of institutionalized second-tier work? To that end we trace workers' labour market pathways over a considerable length of time. We find that a substantial share of women find a way out of vulnerable labour market situations through the scheme. However, a very significant number enter from steady employment. This is clearly at odds with the original objective of offering a stepping stone to women with a precarious labour market position. The scheme also plays an ambivalent role in the labour market integration process of immigrant newcomers. At least in part, the Belgian scheme can be seen as a case of policy overshooting. We suggest some potential improvements.